love in War. Family violence in andahuaylas during the internal armed conflict - Valer Jaime, Kaarina M. (2013)
olitical violence in the decades of 80 and 90 not only involved two forces clashed in a fight blindly and uneven, which committed crimes and human rights violations. It was also a scene of conflict and violence as it relates to the daily life of people, their emotions, to relationships and family. Thus, for the author is important to reflect on violence in the family, violence against women and in this case, against women who were related, in different ways-with counterinsurgency forces members who came to the “emergency zones “in this case the province of Andahuaylas, Apurimac department, during the armed conflict and in subsequent years generating” other victims “product of militarization of these peoples, damages are not so easily, especially in the interior of the people.